ECC2: Error correcting code and elliptic curve based cryptosystem - Zhang, Fangguo; Zhang, Zhuoran; Guan, Peidong (Information sciences, 2020)
•We reconsider the use of algebraic geometry codes in cryptography.•Applying list decoding algorithms to get smaller key size.•An algorithm to generate secure elliptic codes which can resist known structure attacks is presented.•An IND-CPA variant of post-quantum McEliece cryptosystem is proposed. Code-based cryptography has aroused wide public concern as one of the main candidates for post quantum cryptography to resist attacks against cryptosystems from quantum computation. However, the large key size becomes a drawback that prevents it from wide practical applications although it performs pretty well on the speed of both encryption and decryption. The use of algebraic geometry codes is considered to be a good solution to reduce the key size, but the special structures of algebraic geometry codes results in lots of attacks including Minder’s attack. To cope with the barriers of large key size as well as attacks from the special structures of algebraic codes, we propose a code-based encryption system using elliptic codes. The special structure of elliptic codes helps us to effectively reduce the size of secret key. By choosing the rational points carefully, we build elliptic codes whose minimum weight codeword is hard to sample. Such codes are used in constructing encryption systems such that Minder’s attacks can be resisted. More importantly, we apply the list decoding algorithm in the decryption process thus more errors beyond half of the minimum distance of the code could be corrected, which is the key point to resist other known attacks for algebraic geometry codes based cryptosystems. Our implementation shows that the proposed encryption system performs well on the key size and ciphertext expansion rate.